Exploring Ductility in Dental Ceramics. (November 2022) - Alves, L.M.M.; Rodrigues, C.S.; Vardhaman, S.; Saunders, C.; Schneider, J.M.; Lawn, B.R.; Zhang, Y.
Two damage regimes—"brittle" and "ductile"—have been identified in the literature on ceramic grinding, machining, grit blasting, and wear. In the brittle regime, the damage mechanism is essentially crack formation, while in the ductile region, it is quasiplasticity. Onset of the brittle mode poses the greater threat to strength, so it becomes important to understand the mechanics of ductile–brittle thresholds in these materials. Controlled microcontact tests with a sharp indenter are employed to establish such thresholds for a suite of contemporary computer-aided design/computer-aided manufacturing dental ceramics. Plots of flexural strength S versus indentation load P show a steep decline beyond the threshold, consistent with well-established contact mechanics relations. Threshold dimensions occur on a scale of order 1 µm and contact load of order 1 N, values pertinent to practical grit finishing protocols. The ductile side of ceramic shaping is accessed by reducing grit sizes, applied loads, and depths of cut below critical levels. It is advocated that critical conditions for ductile shaping may be most readily quantified on analogous S ( P ) plots, but with appropriate machining variable (grit size, depths of cut, infeed rate) replacing load P . Working in the ductile region offers the promise of compelling time and cost economies in prosthesis fabrication and preparation.